The use of standard operating procedures in day case anterior cruciate ligament reconstruction. - Khan, T; Jackson, W; Beard, D; Marfin, A; Ahmad, M; Spacie, R; Jones, R; Howes, S; Barker, K; Price, A (2012)
The current rate of day-case anterior cruciate ligament reconstruction (ACLR) in the UK remains low. Although specialised care pathways with standard operating procedures (SOPs) have been effective in reducing length of stay following some surgical procedures, this has not been previously reported for ACLR. We evaluate the effectiveness of SOPs for establishing day-case ACLR in a specialist unit. Fifty patients undergoing ACLR between May and September 2010 were studied prospectively ("study group"). SOPs were designed for pre-operative assessment, anaesthesia, surgical procedure, mobilisation and discharge. We evaluated length of stay, readmission rates, patient satisfaction and compliance to SOPs. A retrospective analysis of 50 patients who underwent ACLR prior to implementation of the day-case pathway was performed ("standard practice group"). Eighty percent of patients in the study group were discharged on the day of surgery (mean length of stay=5.3h) compared to 16% in the standard practice group (mean length of stay=21.6h). This difference was statistically significant (p<0.05, Mann-Whitney U test). All patients were satisfied with the day case pathway. Ninety-two percent of the study group were discharged on the day of surgery when all SOPs were followed and 46% where they were not. High rates of day-case ACLR with excellent patient satisfaction can be achieved with the use of a specialised patient pathway with SOPs.